PENGARUH METODE TALAQQI TERHADAP KEMAMPUAN MEMBACA AL-QUR'AN SANTRI : THE INFLUENCE OF THE TALAQQI METHOD ON STUDENTS' AL-QUR'AN READING ABILITY - Maulana Yuhana, Aliyan; Muahammad Arif Annaoval; Anwar, Syamsul (STIT Sirojul Falah Bogor, 2023)
This research is motivated by that there are many modern methods of reading the Qur'an, however the Al-Fadlilah Limbangan Al-Qur'an Islamic Boarding School still uses the classical method, the method used there in learning the Qur'an is using the talaqqi method . The talaqqi method is a method used in learning to read the Al-Qur'an, where the teacher and students face each other directly, the teacher gives an example of reading the Al-Qur'an verses well and correctly and then the students follow along, in this way, the teacher can also pay attention to the reading. students directly and can find out where the students' mistakes are.